Progressive damage analysis of PFRP double-lap bolted joints using explicit finite element method. (15th September 2016) - Du, Ao; Liu, Yuqing; Xin, Haohui; Zuo, Yize
Abstract: To numerically investigate failure behavior of pultruded fiber reinforced polymer (PFRP) bolted joints, a progressive damage analysis (PDA) material model integrating nonlinear shear response, Hashin-type failure criteria and strain-based continuous degradation rules was proposed in the present study. The PDA model was implemented via user subroutine VUMAT, detailed 3D finite element models were established in Abaqus/Explicit. Experiments were conducted to validate the proposed PDA model. Result shows that explicit finite element method is computational efficient and can effectively avoid convergence problem. The predicted joint loading response correlates well with the test result. The FE model can accurately capture various failure modes including bearing, shear-out and net-tension and reveal failure propagation and damage mechanism of PFRP bolted joints. Emergence of first fiber compression failure is found to be a good indicator to identify the load at which the load–displacement response becomes nonlinear.